2005
DOI: 10.1016/j.aaen.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the past to inform the future – A survey of consultant nurses in emergency care

Abstract: Summary This paper reports the findings of a survey of UK consultant nurses in emergency care. The purpose of the survey was to elicit information regarding level of preparation for the consultant nurse role, the use of formal competency frameworks, current clinical scope of practice and perspectives on future preparation for the role. A semi-structured questionnaire was emailed to consultant nurses in emergency care. Respondents had an average of only 2 years in post and for 24% of respondents this was their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 7 publications
1
32
1
Order By: Relevance
“…Would the 'essence' of nursing be lost and would the concept of role substitution be reinforced by following a similar programme of preparation? It could also be argued that a major issue, which arises from both the literature and also from the respondents in this study, is the ambiguity surrounding this role and where it lies within organisations and the professional hierarchy in the NHS (Woodward et al, 2005;Charters et al, 2005). Nursing and in particular the role of the consultant nurse requires the development of a stronger professional identity rather than the erosion of this.…”
Section: Misunderstanding Of Roles Was Another Barrier Identifiedmentioning
confidence: 91%
“…Would the 'essence' of nursing be lost and would the concept of role substitution be reinforced by following a similar programme of preparation? It could also be argued that a major issue, which arises from both the literature and also from the respondents in this study, is the ambiguity surrounding this role and where it lies within organisations and the professional hierarchy in the NHS (Woodward et al, 2005;Charters et al, 2005). Nursing and in particular the role of the consultant nurse requires the development of a stronger professional identity rather than the erosion of this.…”
Section: Misunderstanding Of Roles Was Another Barrier Identifiedmentioning
confidence: 91%
“…Successive studies have identified that the introduction of new roles at organisational level has mixed results (Read et al, 2001;Guest et al, 2004;Charters et al, 2005;Booth et al, 2006;Lathlean, 2007). New roles are ambiguous until they become established (Martin and Hutchinson, 1999) leading to difficulties in developing clear role definitions and role boundaries (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…These posts will vary slightly across the UK, but all should have at least 50% clinical commitment. Previous work has identified that undertaking research, interpreting research and translating findings into clinical practice still remained a challenge (Charters et al, 2005;Woodward et al, 2005).…”
Section: Introductionmentioning
confidence: 99%